Gauging the ethical sensitivity of accounting students: the effect of money attitudes - Owusu, G.M.Y.; Bekoe, R.A.; Effah, N.A.A.; Otchere, O.A.S. (Emerald Publishing Limited, 2021)
Purpose – This paper aims to examine the attitude of accounting students towards money and their ethical perceptions, and ascertains whether ethical perception of students could be influenced by their attitudes towards money. Design/methodology/approach – A survey method of research was adopted, and a set of questionnaires based on the money ethic scale (MES) and existing ethical scenarios was administered to the target respondents. The MES was subjected to an exploratory factor analysis to examine its dimensionality and, by means of a cluster analysis, the respondents were classified based on similarities in attitude towards money. The relationship between attitude towards money and ethical perception was ascertained by means of a multivariate analysis of variance (MANOVA) test. Findings – The results suggest the respondents are generally ethically oriented and that the females are more ethical than males. Differences exist in terms of the attitude of respondents towards money and the MANOVA results show that money attitudes are good predictors of ethical perceptions of students. Research limitations/implications – Findings of this study demonstrate that an understanding of individuals’ attitude towards money may be an important way of predicting how they will behave when faced with ethical dilemmas. Originality/value – The analysis makes an important contribution to prior literature by highlighting the effect of money attitude on ethical perception.
Research Article
Keywords: Structural equation modelling; Business ethics; Accounting students; Ethical sensitivity; Money attitudes